Pengaruh Naungan dan Jenis Aksesi Terhadap Pertumbuhan dan Hasil Kacang Bambara (Vigna subterranea (L.) Verdc) - Al Hamdi, Muhammad Fauzan Farid; Kusumawardani, Mawar; Handayani, Dian Purnami; Astuti, Hanifah Dwi; Pruwita, Adika Trias (Universitas Islam Malang, 2024)
Bambara groundnut has potential to be expanded in dry land and cover crops. The aim of this research is to determine the effect of shade and type of accession on the growth and yield of Bambara bean plants. The research was conducted in Dukuh Tanjung, Umbulmartani Village, Kec. Ngemplak, Kab. Sleman during the dry season. The design used was a Randomized Complete Block Split-Plot Design with two factors. The main factor is shade and no shade treatment, while the subsidiary factor is the type of accession which consists of 6 local accessions. The results showed that (1) the Sumedang Brown and Bogor accessions had the best vegetative growth based on the variables of plant height and number of trifoliate leaves at 5 WAP. (2) The Sumedang Brown and Bogor accessions had the fastest flowering time. (3) The Madura, Gresik and Jampang Tengah Sukabumi accessions had the highest number of pods. (4) 50% shade treatment can reduce pod production in the Jampang Tengah Sukabumi and Gresik accessions.